Docetaxel, cisplatin, and fluorouracil chemotherapy for metastatic or unresectable locally recurrent anal squamous cell carcinoma (Epitopes-HPV02): a multicentre, single-arm, phase 2 study. Issue 8 (August 2018) - Kim, Stefano; François, Eric; André, Thierry; Samalin, Emmanuelle; Jary, Marine; El Hajbi, Farid; Baba-Hamed, Nabil; Pernot, Simon; Kaminsky, Marie-Christine; Bouché, Olivier; Desrame, Jérôme; Zoubir, Mustapha; et al.
Summary: Background: The incidence of anal squamous cell carcinoma has been increasing markedly in the past few decades. Currently, there is no validated treatment for advanced-stage anal squamous cell carcinoma. Therefore, we aimed to validate the clinical activity and safety of docetaxel, cisplatin, and fluorouracil (DCF) chemotherapy in patients with metastatic or unresectable locally recurrent anal squamous cell carcinoma. Methods: We did a multicentre, single-arm, phase 2 study. We recruited patients from 25 academic hospitals, cancer research centres, and community hospitals in France who were aged 18 years or older with histologically confirmed anal squamous cell carcinoma, with metastatic disease or with unresectable local recurrence; an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1; and with at least one evaluable lesion according to the Response Evaluation Criteria in Solid Tumors (version 1.1). Chemotherapy-naive patients received either six cycles of standard DCF (75 mg/m 2 docetaxel and 75 mg/m 2 cisplatin on day 1 and 750 mg/m 2 per day of fluorouracil for 5 days, every 3 weeks) or eight cycles of modified DCF (40 mg/m 2 docetaxel and 40 mg/m 2 cisplatin on day 1 and 1200 mg/m 2 per day of fluorouracil for 2 days, every 2 weeks), which were administered intravenously. The choice between the standard versus modified regimens was recommended based on, but not limited to, age (≤75 years vs >75 years) and ECOG performance status (0 vs 1). The primary endpoint was investigator-assessed progression-free survival at 12 months from the first DCF cycle; for the primary endpoint to be met, at least 11 (17%) of 66 enrolled patients had to be alive without disease progression at 12 months. Efficacy and safety analyses were done in a modified intention-to-treat population, defined as all patients who were evaluable for progression at 12 months who received at least one cycle of DCF. This trial is registered atClinicalTrials.gov, numberNCT02402842, and the final results are presented here. Findings: Between Sept 17, 2014, and Dec 7, 2016, we enrolled 69 patients. Of these patients, three did not receive DCF. Of the 66 patients who received treatment, 36 received the standard DCF regimen and 30 received modified DCF. The primary endpoint was met: 31 (47%) of 66 patients were alive and progression free at 12 months. 22 (61%) of 36 patients who received the standard DCF regimen and 18 (60%) of 30 patients who received the modified DCF regimen had disease progression at data cutoff. 46 (70%) of 66 patients had at least one grade 3–4 adverse event (30 [83%] of 36 in the standard DCF regimen and 16 [53%] of 30 in the modified DCF regimen). The most common grade 3–4 adverse events were neutropenia (15 [23%]; eight [22%] for standard DCF vs seven [23%] for modified DCF), diarrhoea (12 [18%]; nine [25%] vs three [10%]), asthenia (ten [15%]; eight [22%] vs two [7%]), anaemia (ten [15%]; six [17%] vs four [13%]), lymphopenia (eight [12%]; three [8%] vs five [17%]), mucositis (seven [11%]; seven [19%] vs none), and vomiting (seven [11%]; five [14%] vs two [7%]). No grade 4 non-haematological adverse events and febrile neutropenia were observed with modified DCF, whereas three (8%) grade 4 non-haematological adverse events and five (14%) cases of febrile neutropenia were reported with standard DCF. 97 serious adverse events were reported (69 in patients who received the standard DCF regimen [61 drug-related] and 28 in those given the modified DCF regimen [14 drug-related]). No treatment-related deaths were recorded. Interpretation: Compared with standard DCF, modified DCF provided long-lasting response with good tolerability in patients with metastatic or unresectable locally recurrent anal squamous cell carcinoma with ECOG performance status of 0–1 in the first-line setting, and therefore could be considered as a new standard of care for these patients. Regarding the elevated risk of high-grade and serious adverse events and febrile neutropenia, standard DCF cannot be recommended in this situation. Funding: Besançon University Hospital and Ligue contre le cancer Grand-Est.